2024
DOI: 10.3389/fphar.2023.1231006
|View full text |Cite
|
Sign up to set email alerts
|

Bioactivity and toxicity of coumarins from African medicinal plants

Godwin Anywar,
Emmanuel Muhumuza

Abstract: Introduction: Coumarins are naturally occuring metabolites from plants and a few micro-organisms. They have been widely used in the food and drug industry in their natural or synthetic forms. Numerous coumarins possess several biological activities such as anti-inflammatory, anti-ulcers, anti-tumour, anti-microbial, anti-coagulant. The aim of this study was to assess the bioactivity, and toxicity of coumarins from African medicinal plants.Methods: We searched online databases and search engines such as PubMed,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 86 publications
0
1
0
Order By: Relevance
“…These compounds have been documented to exhibit diverse biological effects, including antioxidant and antibacterial properties (Karimi et al, 2015). Many coumarins exhibit various biological properties, including anti-inflammatory, anti-ulcer, anti-tumor, antimicrobial, and anticoagulant activities (Anywar & Muhumuza, 2023). Cedillo-Cortezano et al (2024) reported that essential oils, flavonoids, and phenolic compounds have wound healing properties.…”
Section: Phase Separationmentioning
confidence: 99%
“…These compounds have been documented to exhibit diverse biological effects, including antioxidant and antibacterial properties (Karimi et al, 2015). Many coumarins exhibit various biological properties, including anti-inflammatory, anti-ulcer, anti-tumor, antimicrobial, and anticoagulant activities (Anywar & Muhumuza, 2023). Cedillo-Cortezano et al (2024) reported that essential oils, flavonoids, and phenolic compounds have wound healing properties.…”
Section: Phase Separationmentioning
confidence: 99%